Interventions to improve multicultural counseling competence: a systematic review - Xian, Chen Ke; Hassan, Siti Aishah (Human Resource Management Academic Research Society, 2022)
Purpose: To evaluate the effectiveness of counselor training interventions in improving multicultural competence of counseling professionals. Methods: A systematic review of studies published between 2010 and 2016 was conducted and the Scopus electronic database was searched. Results: 245 articles were identified in the initial search and twelve articles met the inclusion / exclusion criteria which are then extracted for analysis. There were four main categories of interventions found: service learning, cultural immersion, culturally tailored program and traditional counseling graduate program. All of the studies except traditional training programs showed positive effects on the multicultural competence of the participants. Conclusions: The findings of this review indicate that experiential learning and culturally tailored programs resulted to improvement on the multicultural competence of the participants. Due to heterogeneity in the reviewed studies, it is difficult to compare the studies and evaluate for the most feasible and effective intervention. Future research should focus on developing a standardize framework for multicultural competence and measure for both counsellor and client outcomes.